Data security and consumer trust in FinTech innovation in Germany. (12th March 2018) - Stewart, Harrison; Jürjens, Jan
Abstract : Purpose: The purpose of this study is to empirically analyse the key factors that influence the adoption of financial technology innovation in the country Germany. The advancement of mobile devices and their usage have increased the uptake of financial technology (FinTech) innovation. Financial sectors and startups see FinTech as a gateway to increase business opportunities, but mobile applications and other technology platforms must be launched to explore such opportunities. Mobile application security threats have increased tremendously and have become a challenge for both users and FinTech innovators. In this paper, the authors empirically inspect the components that influence the expectations of both users and organizations to adopt FinTech, such as customer trust, data security, value added, user interface design and FinTech promotion. The empirical results definitely confirm that data security, customer trust and the user design interface affect the adoption of FinTech. Existing studies have used the Technology Acceptance Model (TAM) to address this issue. The outcomes of this study can be used to improve the performance of FinTech strategies and enable banks to achieve economies of scale for global intensity. Design/methodology/approach: In this paper, the authors empirically consider factors that influence the expectations of both users and organizations in adopting FinTech, such as customer trust, data security, value added, the user design interface and FinTech promotion. The results confirm that customer trust, data security and the user design interface affect the adoption of FinTech. This research proposes a model called "Intention to adopt FinTech in Germany, " constructs of which were developed based on the TAM and five additional components, as identified. The outcomes of this study can be used to improve the performance of FinTech strategies and enable banks to achieve economies of scale for global intensity. Findings: The authors demonstrated that the number of mobile users in Germany is rapidly increasing; yet the adoption of FinTech is extremely sluggish. It is intriguing to reckon that 99 per cent of respondents had mobile devices, but only 10 per cent recognized FinTech. Further, it is significantly discouraging to perceive that only 10 of the 209 respondents had ever used FinTech services, representing under 1 per cent of the surveyed respondents. It is obvious that the FinTech incubators and banks offering FinTech services need to persuade their customers regarding the usefulness and value added advantages of FinTech. This study has been carried out to determine the key factors that influence and provoke FinTech adoption. Research limitations/implications: There are a few limitations in this study. Initially, this study focuses on FinTech implementation in Germany and not the whole of Europe. In addition, demographic and regional factors could be consolidated to inspect their particular impact on the intention to use FinTech services, particularly among younger users with a high interest in technology. Without these constraints, the authors could have gathered additional data for a more robust result and obtained new knowledge to further upgrade polices to enhance the FinTech adoption process. Future analysts can assist exploration of this topic by altering determinants in the unified theory of acceptance and use of technology model. Additionally, because the cluster sampling technique was used, the reported outcomes are not 100 per cent generalized to the German population. To accomplish a complete generalization, a basic random sampling strategy for the whole population is essential. The authors could also alleviate some limitations by examining how online vendors are performing with regard to FinTech to satisfy the needs of customers via case studies. Practical implications: This study was conducted in Germany and might have produced different results if held in other countries, as technology acceptance is different in a different environment. For instance, the authors suspect that the results would be somewhat different, were the research to be conducted in the United Kingdom, where take-up of FinTech appears to be far greater than in Germany. Therefore, the authors' results are only generalized for the country of Germany and not other geographical areas. Furthermore, respondents may have been influenced by past experiences about FinTech usage which might have led them to neglect to answer some questions. In spite of this, this study did not consider the influence of moderating variables such as age, education and FinTech services experience. The authors also neglected social impact and control factors, as their corresponding items disregarded the instrument dependability. Accordingly, the authors could not quantify social impact and control factors on FinTech use. Social implications: The outcomes of this study can be used to improve the performance of FinTech strategies and enable banks to accomplish economies of scale for global intensity. The authors do hope that this paper will serve to encourage FinTech innovators in their approach to FinTech and enable FinTech researchers to use past work with more prominent certainty, resulting in rigid hypothesis improvement in the future. Originality/value: A considerable amount of revenue has been invested in the information technology (IT) infrastructure of banks to enhance their performance, but investment in IT remains a substantial risk regarding the return on investment (Carlson, 2015 ). Most banks and financial organizations around the globe are engaging in an extreme pressure from their customers and competitors to enhance IT.